Incidence of K1 antigen in Escherichia coli isolated from blood and cerebrospinal fluid of patients in the United Kingdom. Issue 10 (October 1977) - Cheasty, T; Gross, R J; Rowe, B
Abstract : Altogether 411 cultures of Escherichia coli isolated from blood and 60 from cerebrospinal fluid (CSF) of patients in the United Kingdom were identified biochemically and serologically. They were tested for the presence of K1 antigen by an antiserum-agar method using horse meningococcus group B antiserum and by slide agglutination using E. coli 07.K1.H-antiserum. In total 71 cultures from blood (17%) and 29 from CSF (48%) gave positive results by both methods and were considered to possess the K1 antigen. Among the cultures from patients less than 3 years of age the K1 antigen was found significantly more often in those isolated from CSF (53%) than in those from blood (29%). The K1 antigen was found significantly more frequently in cultures isolated from the blood of patients less than 3 years old (29%) than in those from the blood of older patients (13%). Cultures which gave negative results in the slide agglutination test also gave negative results by the antiserum-agar method but positive results obtained by slide agglutination were not always confirmed using the antiserum-agar technique. Slide agglutination was considered to be valuable for the elimination of K1 negative cultures, but positive results required confirmation using the antiserum-agar method.